Etiologi Multifaktorial dan Tantangan Diagnostik Disfagia pada Pasien Geriatri Usia Sangat Lanjut : Laporan Kasus dan Tinjauan Skoping - Iwan Setiawan Adji; Zahira Husna Aflaha Khansa Siswaya; Hanif Nur Khairuddin; Eillena Noxie Azzahra; Namira Aisya Devi; Sultan Bayu Fahmi (Universitas Muhamadiyah Manado, 2026)
Dysphagia in extremely elderly patients represents a significant clinical challenge because it is frequently associated with frailty, malnutrition, and an increased risk of aspiration. Multifactorial etiologies and atypical clinical manifestations may complicate diagnosis and delay appropriate management. This study aimed to describe the diagnostic evaluation and clinical findings of dysphagia in an extremely elderly patient through a case report supported by a scoping review. A 105-year-old woman with chronic progressive dysphagia underwent comprehensive assessment, including physical examination, upper gastrointestinal endoscopy, histopathological evaluation, and chest radiography. Relevant literature on dysphagia in geriatric populations was reviewed to provide contextual understanding of diagnostic challenges and underlying etiologies. The evaluation revealed chronic active gastritis and a hamartomatous polyp in the gastroesophageal region without evidence of malignancy. Comprehensive assessment successfully excluded malignant and acute obstructive causes, emphasizing the complexity of dysphagia diagnosis in extremely elderly individuals with frailty and aspiration risk. These findings underscore the importance of endoscopic and histopathological examinations in distinguishing benign from malignant etiologies and support early recognition of multifactorial non-malignant causes to optimize clinical management and reduce the risk of adverse outcomes in this vulnerable population